2011
DOI: 10.1128/jcm.01578-10
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Identification of Mycobacterial Isolates to the Species Level and Determination of Tuberculosis Drug Resistance by PCR Followed by Electrospray Ionization Mass Spectrometry

Abstract: Mycobacterium tuberculosis that is resistant to both isoniazid (INH) and rifampin (RIF) is spreading. It has become a public health problem in part because the standard culture methods used to determine the appropriate treatment regimen for patients often take months following the presumptive diagnosis of tuberculosis. Furthermore, the misidentification of nontuberculosis mycobacteria (NTM) in patients presumably suffering from tuberculosis results in additional human and health care costs. The mechanisms of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
1
27
0
2
Order By: Relevance
“…This low proportion of PGG1 and consequently of Beijing type observed in the studied group is similar to that reported in Central and Western Europe 3 and in contrast with the higher prevalence rates from neighbouring Ukraine and North-Western Russia. 5 This observation needs to be confirmed by further studies, since the present study was not designed for prevalence estimation.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This low proportion of PGG1 and consequently of Beijing type observed in the studied group is similar to that reported in Central and Western Europe 3 and in contrast with the higher prevalence rates from neighbouring Ukraine and North-Western Russia. 5 This observation needs to be confirmed by further studies, since the present study was not designed for prevalence estimation.…”
Section: Discussionmentioning
confidence: 92%
“…5 A large study performed on 1340 samples originating from different populations showed very good results for drug resistance detection with PCR/ESI-MS, with sensitivities of 96.4% for RIF and 89.2% for INH and specificities of 98.6% and 95.8% for RIF and INH, respectively. 5 In another study performed on 48 samples the sensitivity and specificity values were 100% and 93.8% for INH and 100% and 92.3% for RIF when PCR/ESI-MS was compared to phenotypic DST. 7 Similarly, in the present study PCR/ESI-MS had sensitivities in detecting INH and RIF resistance of 100% and 92% respectively and specificities exceeding 95% to both RIF and INH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of mass spectrometry for the identification of Mtb complex from culture isolates may replace current standards such as biochemical analysis, nucleic acid hybridization probes, and DNA sequencing due to the ability of mass spectrometry to rapidly and accurately identify Mtb in a cost-effective manner while minimizing technologist hands-on time and effort (Saleeb et al, 2011). Although still in it's infancy in the diagnostic microbiology laboratory, this technology may also have utility in predicting drug resistance patterns and evaluating epidemiologic groups (Bouakaze et al, 2011;Massire et al, 2011;Schurch et al, 2011).…”
Section: Future Directionsmentioning
confidence: 99%